2021
DOI: 10.7759/cureus.19942
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Mucosal Health by NLR, CRP x NLR and MPV in Ulcerative Colitis: Can Their Availability Change According to Treatment Options?

Abstract: IntroductionMucosal healing is the main treatment goal in ulcerative colitis (UC). Many noninvasive parameters have been used in clinical practice to assess mucosal healing. In this study, we aimed to evaluate the effectiveness of neutrophil-lymphocyte ratio (NLR), C-reactive protein (CRP) x NLR and mean platelet volume (MPV) in predicting mucosal health. MethodThis study was designed as a retrospective and single-center. A total of 165 patients, 126 active and 39 in remission, were included in this study. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…They reported that the active phase of the disease could be detected with MPV cut-off level <8.2 fL (60.0% Sensitivity and 77.5% Specificity) and PDW cut-off level <16.6 fL (60.0% Sensitivity and 77.5% and Specificity). Cifci et al [ 11 ] found that UC disease severity was positively correlated with CRP, and PLT levels and negatively correlated with MPV. They reported that PLT level was predictive in the detection of MH (Cut-off value <278.6x10 3 /µL; Sensitivity and 72.2% Specificity 46.2%), but MPV levels were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…They reported that the active phase of the disease could be detected with MPV cut-off level <8.2 fL (60.0% Sensitivity and 77.5% Specificity) and PDW cut-off level <16.6 fL (60.0% Sensitivity and 77.5% and Specificity). Cifci et al [ 11 ] found that UC disease severity was positively correlated with CRP, and PLT levels and negatively correlated with MPV. They reported that PLT level was predictive in the detection of MH (Cut-off value <278.6x10 3 /µL; Sensitivity and 72.2% Specificity 46.2%), but MPV levels were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of platelets plays a role in determining and managing mucosal inflammation in the active phase of UC by affecting cytokine levels, such as IL-1, beta-tromboglobulin, platelet-derived growth factor, platelet activation factor, platelets factor 4 [10,16]. Finally, it is known that MPV and PDW levels show influence during exacerbations of chronic inflammation [8][9][10][11][12][13]. In the present study, we aimed to determine the predictive value of PLT, MPV, and PDW levels in detecting disease activation, disease severity, and MH in patients with UC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations